(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article examines the role of television as a medium of cultural identity formation in the context of globalization. It analyzes theoretical approaches of Western and Russian scholars, highlighting television’s dual function as both a preserver of traditions and a driver of cultural change. Special attention is paid to the influence of television genres, including news, documentaries, and entertainment programs, in shaping collective memory and values. The article also discusses the impact of globalized television on youth culture and the hybridization of identities. The study concludes that television is both a unifying force in contemporary society.